Effect of Drip Irrigation of Sunflower Crop on Soil Meliorative Status (Texas Journal of Agriculture and Biological Sciences, 2022)
Many decisions and decrees are being adopted in the Republic on the purposeful use of water resources. On September 6, 2019, the strategy for the development of agriculture in Uzbekistan in 2020- 2030 was developed. According to the concept of water management development of the Republic of Uzbekistan for 2020-2030, the areas where water-saving technologies have been introduced are 2 million. ha, including drip irrigation technology for 600,000 ha. applied to the area, 35-40% (3.5-4 billion cubic meters) of water is saved per year. This is 298,000 ha at the expense of water. disused areas can be redeveloped.